Effect of Chinese herbal medicine pack hot compress on relieving the pruritus in diabetes patients with deficiency of both Qi and Yin syndrome (药包热敷器治疗气阴两虚型糖尿病皮肤瘙痒效果观察) - YUAN Zheng (袁铮); LIU Qing (刘青); CHEN Yuanyuan (陈媛媛); LI wei (李伟) (中西医结合护理)
Objective To investigate effect of Chinese herbal medicine pack hot compress on relieving skin itching symptom in diabetes patients. Methods From January 2024 to May 2024, 64 diabetes patients with deficiency of both Qi and Yin syndrome were divided into the control group and the intervention group according to the random number table grouping method, of 32 patients in each group, Both groups were administered the same basic treatment, The control group were given oral loratadine tablets, 10 mg orally once after a daily breakfast, 14 days; The intervention group was treated with Chinese herbal medicine pack hot compress. Using Traditional Chinese Medicine syndrome integral scale, Visual Analogue Scale(VAS) and Pittsburgh Sleep Quality Index (PSQI) to measure the degree of pruritus symptoms and sleep quality before enrollment and 14 days after treatment. Results The pruritus response rate in the intervention group was 96. 88% (31/32) and 75%(24/32) in the control group, with as significant difference (P＜0. 05). The total score of TCM integral scale was (16. 75 ± 4. 23) in the intervention group and (27. 94 ± 3. 29) in the control group, with as significant difference(t=11. 81, P＜0. 05); The VAS score of patients in intervention group was (2. 08 ± 0. 63), which was lower than (4. 55 ± 1. 21) of patients in the control group (t=10. 24, P＜0. 05); PSQI score of patients in the intervention group was (9. 06 ± 2. 75), which was lower than (10. 66 ± 2. 70) of patients in the control group (t= 2. 34, P＜0. 05). Conclusion The clinical effect of using Chinese herbal medicine pack hot compress to treat pruritus is remarkable, which can reduce the skin itching symptoms and improve the sleep quality of patients. (目的 探讨使用药包热敷器治疗糖尿病患者皮肤瘙痒的效果。方法 2024年1月—5月, 选取贵州中医药大学第一附属医院内分泌科住院的气阴两虚型糖尿病皮肤瘙痒患者64例为研究对象, 按照随机数字表分组法分为对照组和干预组, 每组32例。两组给予相同的基础治疗, 对照组均予口服氯雷他定片, 每日早餐后1次10 mg口服, 治疗14 d; 干预组给予中医特色技术药包热敷器治疗。利用中医证候总积分评估表、视觉模拟评分尺(VAS)、匹兹堡睡眠质量指数量表(PSQI), 在入组前和治疗后14 d分别进行患者瘙痒症状、瘙痒视觉感知、睡眠质量的测试, 评估患者皮肤瘙痒及睡眠改善情况。结果 干预组的瘙痒缓解率为96. 88%(31/32), 对照组为75%(24/32), 差异有统计学意义(P＜0. 05)。治疗后, 干预组中医证候总积分为(16. 75±4. 23)分, 对照组为(27. 94±3. 29)分, 干预组评分低于对照组(t=11. 81, P＜0. 05); 干预组患者瘙痒VAS评分为(2. 08±0. 63)分, 对照组为(4. 55±1. 21)分, 干预组评分低于对照组(t=10. 24, P＜0. 05); 干预组患者PSQI量表评分为(9. 06±2. 75)分, 对照组为(10. 66±2. 70)分, 干预组评分低于对照组(t=2. 34, P＜0. 05)。结论 临床使用药包热敷器治疗气阴两虚型糖尿病皮肤瘙痒效果明确, 能够减轻皮肤瘙痒症状, 改善患者睡眠质量, 提高生活质量, 具有推广价值。)